2008
DOI: 10.1155/2008/639829
|View full text |Cite
|
Sign up to set email alerts
|

An Antithrombin-Heparin Complex Increases the Anticoagulant Activity of Fibrin Clots

Abstract: Clotting blood contains fibrin-bound thrombin, which is a major source of procoagulant activity leading to clot extension and further activation of coagulation. When bound to fibrin, thrombin is protected from inhibition by antithrombin (AT) + heparin but is neutralized when AT and heparin are covalently linked (ATH). Here, we report the surprising observation that, rather than yielding an inert complex, thrombin-ATH formation converts clots into anticoagulant surfaces that effectively catalyze inhibition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To overcome some of the limitations of UFH, our laboratory has developed a covalent complex of antithrombin and heparin (ATH) with high anticoagulant activity (25). Numerous in vitro and in vivo investigations involving ATH have led to results showing potential clinical advantages of ATH over UFH (25)(26)(27)(28)(29)(30). More specifically, we have demonstrated that ATH inhibits FXa within a prothrombinase on an artificial phospholipid surface much better than AT+UFH (24).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome some of the limitations of UFH, our laboratory has developed a covalent complex of antithrombin and heparin (ATH) with high anticoagulant activity (25). Numerous in vitro and in vivo investigations involving ATH have led to results showing potential clinical advantages of ATH over UFH (25)(26)(27)(28)(29)(30). More specifically, we have demonstrated that ATH inhibits FXa within a prothrombinase on an artificial phospholipid surface much better than AT+UFH (24).…”
Section: Introductionmentioning
confidence: 99%